THE EFFECT OF KETONE BODIES ON SOME BLOOD PARAMETERS IN PREGNANT SHEEP - Sengaliyev, Y. M.; Kushmukhanov, Zh. S.; Duimbaev, D. A.; Muldagaliyev, M. Kh. (Жәңгір хан атындағы БҚАТУ, 2025)
One of the main issues currently in veterinary medicine is the problem of obtaining high fertility and increasing the longevity of queens in animal husbandry. Currently, in sheep farming, we observe the tension of the functional systems of the sheep's body, which work at the peak of a pathological condition that contributes to the development of new diseases. Due to disorders in the body of pregnant animals, the syndrome of feto placenta insufficiency develops, which triggers changes in the fetus / fetuses in the uterus of the mother. In our study, the experimental group of pregnant animals with signs of latent ketosis included sheep in which, when studying the composition of urine, we found ketone bodies in urine of more than 0.5 mmol/l. We have found that when the indicators of ketone bodies increase by 2.3 times more than physiological norms, both the indicators of the fraction — acetoacetic acid with acetone and βhydroxybutyric acid also increases 5.9 and 1.5 times, respectively, buffer base values decrease to 18.41 ± 1.53 mmol/L, glucose concentrations in animals also decrease to 2.25 ± 0.16 mmol/L, as well as a decrease in the coefficient of acetoacetic acid with acetone and β-hydroxybutyric acid to 1.53± 0.28 indicates that we have studied pregnant animals with changes in metabolism in the body, which corresponds to signs of latent ketosis. The results of our study also show that the proportionality of the fraction of the studied ketone bodies of VN to AcAs was reduced by 1.9:1 and we take these data into account as a marker of fatty liver dystrophy, which does not depend on the limit of total ketone bodies in the blood. Changes in the metabolism of the body in pregnant animals disrupt the function of the fetoplacental complex, which leads to stimulation of the metabolic process. We have confirmed an increase in the proportion of ketodiene products and trione binding in the blood of pregnant animals with latent ketosis by 1.75 times. malondialdehyde values in latent ketosis were in the range of 1.125 ± 0.34 mmol/l. Accordingly, markers of metabolism that are commonly used in veterinary medicine for diagnostic purposes in pregnant animals with latent ketosis differ in that they show low sensitivity and have low specificity in comparison with these systems of lipid peroxidation and antioxidant protection. In the future, the results of these studies should be taken into account when studying diseases such as latent and clinical ketosis of pregnant animals as a concept of the occurrence of a change in the function of lipid peroxidation – antioxidant protection in this metabolic pathology.
The effect of ketone bodies on some blood parameters in pregnant sheep / Y. M. Sengaliyev, Zh. S. Kushmukhanov, D. A. Duimbaev, M. Kh. Muldagaliyev . - Текст : непосредственный // "Ғылым, зерттеулер, білім: даму тенденциялары" атты XXV халықаралық ғылыми-практ. конф. жинағы = Сollected papers XXV International scientific and practical conference "Science, research, education: development trends"= «Наука, исследования, образование: тенденции развития»: cб. XXV междунар. науч.-практ. конф. - Орал: Жәңгір хан атындағы БҚАТУ. - 2025. - Р. 20-27 (Uralsk).
Keywords: ketone bodies; sheep; latent ketosis; metabolic disorders; blood; рк; зкату